Advances in VLSI and Embedded Systems Select Proceedings of AVES 2019 - Patel, Zuber; Gupta, Shilpi; Kumar Y. B., Nithin; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
This book presents select peer-reviewed proceedings of the International Conference on Advances in VLSI and Embedded Systems (AVES 2019) held at SVNIT, Surat, Gujarat, India. The book covers cutting-edge original research in VLSI design, devices and emerging technologies, embedded systems, and CAD for VLSI. With an aim to address the demand for complex and high-functionality systems as well as portable consumer electronics, the contents focus on basic concepts of circuit and systems design, fabrication, testing, and standardization. This book can be useful for students, researchers as well as industry professionals interested in emerging trends in VLSI and embedded systems. .
Automated simulator for the validation of bio-impedance devices -- Analysis of Memory-Based Real Fast Fourier Transform Architectures for Low-Area Applications -- Optimization of MEMS-Based Capacitive Sensor with High-k dielectric for Detection of Heavy Metal Ions -- Statistical Analysis of Vehicle Detection in the ITS application for monitoring the traffic and road accident using Internet of Things -- Hamiltonian Mechanics -- FPGA design of SAR type ADC based analog input module for industrial applications -- FPGA Based Implementation of Artifact Suppression and Feature Extraction -- Test Time Reduction using Power Aware Dynamic Clock Allocation to Scan Vectors -- Impact of Spacers in Raised Source/Drain 14 nm technology node.
Keywords: Electronic circuits; Power electronics; Computer-aided engineering; Circuits and Systems; Power Electronics, Electrical Machines and Networks; Computer-Aided Engineering (CAD, CAE) and Design